RELASI INTERSUBJEKTIF DALAM RELASI MANUSIA DENGAN ALLAH DARI ST. AGUSTINUS DAN ST. BONAVENTURA - SUHASSATYA, GABRIEL KRISTIAWAN (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2022)
Humans are creatures created in the image and likeness of God. Therefore, humansalways have a relationship, relationship, and communication with God. In addition,humans are also inseparable from other humans so that there is a relationshipbetween humans with one another. Human relations and relationships with God andhumans with other humans have been established since the first Creation. Theserelationships will always run from age to age up to this modern era. The discussionof human relations with God has been discussed by many thinkers. In modern times,the discussion of the human relationship with God has been discussed by MartinBuber who is a modern-century philosopher of Jewish descent. He discussed it inthe topic of intersubjective relations (I and Thou). In this paper, the authordescribes the intersubjective relationship between Martin Buber and the Christianfaith thought of the great Christian thinker, namely St. Augustine and St.Bonaventure.